(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
In recent decades, sleep disorders have become more widely recognised. Sleep problems impact a large segment of the population and present in a number of ways. Obstructive Sleep Apnoea (OSA) is one of the commonest sleep-related breathing disorder, characterised by recurring bouts of upper airway block while sleeping. The prevalence of OSA in the general population ranges from 9% to 38%1, and at least 13.4% of females worldwide have mild OSA2, among obese individuals in Ahmedabad (Gujarat, India) is 69.11%3, and 81.4 percent in patients with cardiovascular diseases.4 Previously, the prevalence of OSA in men was reported to be about 19.7 percent and 7.4 percent in women in India.5 According to a recent study, OSA is highly prevalent (32.5%) in an Indian population.6 OSA leads to excessive daytime sleepiness (EDS) and people with OSA have twice the rate of motor-vehicle accidents as unaffected people.7 However, awareness of OSA remains low, and the disorder is mainly undiagnosed and unreported in India. As a result, the data presented above may only scratch the surface of the situation. Sleep disorders are not always evident to the person suffering from them. These difficulties lead to occasional involvements with the judicial system. We strive to include the most prevalent connections between sleep disorders and the legal system in this article, such as the problems of extreme sleepiness and transportation, other legal